Soils and geomorphology - Birkeland, Peter W. (Oxford University Press, 1999)
"Soils and Geomorphology, now in its third edition, remains popular among soil scientists, geomorphologists, geologists, geographers, and archeologists. While retaining the useful "factors of soil formation format," it has been extensively revised, incorporating a considerable amount of new research and offering a greater number of topics and examples - particularly in the chapters "Weathering and Soil Development with Time" and "Topography: Soil Relations with Time in Different Climatic Settings." Greater emphasis is placed on the role of dust in pedogenesis, and new data are included on tropical soil development, global soil-loess relations, neotectonics, and reduction processes. Soils and Geomorphology is an ideal text for advanced undergraduate and graduate students in courses on pedology, soil science. Quaternary geology, archeology, and sedimentary petrology."--BOOK JACKET.